MARKETING EFFORTS THROUGH SOCIAL MEDIA ON BRAND EQUITY AND CONSUMER BEHAVIOR - Hery Purnomo; Subagyo, Faisol (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This literature research discusses marketing efforts via social media and their influence on brand equity and consumer behavior. Along with technological developments and increasing internet use, social media has become an important tool in marketing strategies. This study aims to analyze how marketing via social media can increase brand awareness, consumer loyalty and positive perceptions of the brand. This research also examines the impact of consumer interaction and involvement on social media on their purchasing decisions. The methodology used is a literature review. The research results show that social media has a significant role in building brand equity. High interaction and interesting content can create an emotional connection between consumers and brands, which ultimately increases consumer loyalty and purchase intentions. These findings provide practical implications for marketers in designing effective social media strategies and focusing on increasing brand equity and influencing consumer behavior. Significant changes in consumer behavior in recent years reflect shifting values, needs and expectations in an evolving market ecosystem. The focus on sustainability and the environment, the increasingly rapid adoption of e- commerce and online shopping, the demand for personalization, the increasing influence of social media in purchasing decisions, the demand for transparency, and the provision of seamless and interactive digital experiences, are the key factors that today determine consumer behavior.